Ultraselective low temperature steam reforming of methanol over PdZn/ZnO catalysts Influence of induced support defects on catalytic performance - Katarzyna Morawa Eblagon (2014)
The influence of the calcination atmosphere of ZnO precursor (Zn-4(CO)(3)(OH)(6)center dot H2O) on the catalytic performance of a series of PdZn/ZnO catalysts was studied for production of H-2 via low temperature (180 C) direct methanol steam reforming (low temperature-MSR). The catalytic activity and selectivity of PdZn/ZnO were found to be strongly influenced by the calcination atmosphere of ZnO precursor and increased from oxidizing to reducing atmosphere, following the order (O-2 < air < N-2 <H-2). As a result, a very active catalyst was obtained by simply supporting Pd on ZnO calcined in H-2. Further evidence from XPS and TPR analysis indicated that calcination in reducing atmosphere gave rise to a significant increase in the concentration of oxygen vacancies on the surface of ZnO support. Thus, the superb performance of the best catalyst was attributed to the defect chemistry of ZnO support; mainly to the amount of oxygen vacancies present in the interface region, which act as additional active sites for water adsorption and subsequent activation. In addition, the formation of CO was drastically suppressed by replenishment of oxygen vacancies on ZnO support. Thus, it is clear that the abundance of specific active sites on PdZn/ZnO catalyst is strongly influenced by the preparation route of the ZnO support. Additionally, the PdZn alloy was discovered to be unstable under prolonged exposure to CO atmosphere and the stability test under methanol steam reforming conditions showed a 24% drop in conversion over 48 h testing period. This phenomena can have detrimental effect on the performance of this type of catalytic systems in continuous prolonged duty cycle time on-stream.